2021
DOI: 10.1002/cbdv.202100245
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Extracts as Potential Antioxidant, Anti‐Aging, Anti‐Inflammatory, and Whitening Cosmeceutical Ingredients

Abstract: The aim of this research was to investigate and compare the antioxidant, anti-tyrosinase, anti-aging, and antiinflammatory activities of 16 herbal extracts for topical application in cosmetic/cosmeceutical products. Herbal plant materials were extracted by infusion in boiled water for 15 min. The total phenolic content and total flavonoid content of each extract were investigated by the Folin-Ciocalteu and aluminum chloride methods, respectively. Antioxidant activities were investigated using 2,2'-diphenyl-1-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…Sunscreen application containing UV filters is a practical prevention approach to skin photoaging [ 11 , 15 , 16 , 17 ]. However, UV-filter skin-penetration-induced allergies and dermatitis are concerning issues [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sunscreen application containing UV filters is a practical prevention approach to skin photoaging [ 11 , 15 , 16 , 17 ]. However, UV-filter skin-penetration-induced allergies and dermatitis are concerning issues [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to skin-aging problems, oxidative-stress-related obesity and cellulite development have become further intricate aesthetic concerns among consumers. Therefore, prevention and treatment through anti-adipogenic effects that inhibit the preadipocyte differentiation and lipid accumulation of anti-obesity agents have been proposed [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to prevent or reduce oxidative stress, exogenous antioxidants that scavenge free radicals are used. Typical examples of such compounds are α‐tocopherol, ascorbic acid, carotenoids and natural polyphenols [15–19] …”
Section: Introductionmentioning
confidence: 99%
“…is experiment is based on previous research and consulting relevant literature [3,[10][11][12][13][14], and we found that GA, ascorbic acid, EA, rutin, quercetin, and catechol are the main compounds in these fractions. In order to find more quality control compounds, we choose the 1-galloylglucose, GA, TGG, EA, and rutin as detection indicators.…”
Section: Introductionmentioning
confidence: 99%